Distributed computing in a time series analysis system - Yoshikazu Yamamoto; Junji Nakano (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
In this paper, we consider simple and easy distributed computing abilities of the statistical system TISAS (TIme Series Analysis Supporting System). TISAS was mainly 'written in the Tcl / Tk language, and was designed for utilizing full merits of a GUI (Graphical User Interface). We add functions for distributed computing without chaIlenging the style of the TISAS GUI by using TkPVM, which is an implementation of PVM (Parallel Virtual Machine) libraries through Tcl / Tk. We adopt a server client system structure for the new version of TISAS. The server part executes data manipulations and the client part does GUI works. For designing them, we use a Model~ View~Controller framework, which makes our implementation relatively simple.
urn:nbn:de:kobv:11-10050500
Keywords: 330; Statistical system; Distributed computing; Graphical User Interface; Model-View-Controller; PVM; Tcl/Tk